Smaller size‐at‐age menhaden with coastal warming and fishing intensity. Issue 2 (4th October 2017) - Turner, R Eugene
Abstract : The size‐at‐age of one million Brevoortia tyrannus and B. patronus, harvested from Maine to Texas over 65 years, were analysed to determine if there was evidence of changes consistent with the well documented temperature size rules. The average annual weight and length for age 3‐, 4‐ and 5‐year‐old fish declined on both the Atlantic and Gulf of Mexico (GOM) coasts. For example, the average size of a 4‐year‐old fish captured in 2010 from the Atlantic and GOM, relative to an average 4‐year‐old fish captured in 1987, is 15 per cent and 11 per cent lighter, respectively. Small changes in the year‐to‐year size of same‐aged fish were closely related to variations in the annual air temperature (used as a proxy for water temperature) for fish on both coasts. The size‐at‐age of GOM fish are also smaller during overfished periods compared with underfished periods by 10–24 per cent, and decrease by about the same proportion as indicated by temperature changes. The most plausible explanation for these size changes is that they are a consequence of recent coastal and oceanic warming. These reductions in size‐at‐age by temperature and fishing pressure affect egg production, oil yield and prey community for one‐half of the US Atlantic and GOM fish harvest. The future of menhaden fish size‐at‐age will be, it seems, smaller as oceanic temperatures rise. Abstract : The size of menhaden, a commercially‐fished species on the Atlantic and Gulf of Mexico coasts (half of the fisheries harvest) is declining. A warming coastal environment is the plausible cause, with additional shrinkage from fishing pressure. e00044